Empowering School Health Units in Utilizing Ginger-Boiled Water and Green Coconut Water for Dysmenorrhea Relief - Desri Nova; Yeltra Armi; Neneng Fitria Ningsih; Meka Melani Sari; RMI Yusahadi S; Devi Eka Safitri (Global Sustainability Research Institute, 2025)
The purpose of the public discussion is to educate students, particularly teenage girls, on the use of experience materials to treat menstrual pain (dysmenorrhea). This program is implemented by using the School Health Unit as a media outlet to facilitate education and use ginger-boiled water and green coconut water as a substitute for menstrual pain. Through study and instruction, teenage girls learn about the benefits of ginger and green coconut, which contain natural compounds that can help reduce pain. As an easy, safe, and pleasant way to lessen the severity of menstruation, ginger boiled water, which has anti-inflammatory and anti-spasmodic properties, as well as green coconut water, which will be electrolyzed and include antioxidants, is recommended. Along with teaching, this program teaches students how to properly handle and consume both of these materials so they may use them independently. It is hoped that through this activity, teenage girls will have useful solutions to deal with dysmenorrhea and that they will also increase their awareness of the importance of reproductive health.